A Study on Investors’ Expected Rate of Return on their Investments with Special Reference to the Judicial Department Employees of Rajkot - Virani, Varsha; Bhadeshiya, Hardik B. (Indian Journal of Finance, 2012)
Investment means the purchase by an individual of a financial or real asset that produces a return over some future investment period. For achieving this, he/she has to decide on how and where to deploy his savings so that his future requirements for money can be best met. Until the late 1990s, a high interest rate environment characterized India. The impact of any change in interest rates affects the way companies finance their operations. When interest rates are high, companies prefer the raise funds through issue of equity shares rather than bonds and high-cost bank loans. However, in case of falling interest, bank loans become more attractive as a source of finance than equity. So, this means that lower interest rates are bad for the primary market and are good for the secondary markets. Hence, the present study was conducted to know the investors’ expected rate of return with special reference to the Judicial Department employees of Rajkot, Gujarat.